Culture, personality, and mental illness : a perspective of traditional societies - Varma, Vijoy K.; Kala, A. K.; Gupta, Nitin (New Delhi : Jaypee Brothers Medical Publishers, 2009)
Contributed articles.
Includes bibliographical references and index.
Keywords: Cultural psychiatry -- India; Cultural psychiatry -- Developing countries